Chemometric analysis on concentrations and ratios of terpanes and steranes and implications for oils from the cratonic region of the Tarim Basin, NW China - Yuanyuan Bian; Chenxi Zhou; Haizu Zhang; Zhongyao Xiao; Zhaowen Zhan; Shuang Yu; Changchun Pan (Petroleum Research)
More than 2 × 109 tonnes of proved oils have been found in the cratonic region of the Tarim Basin. The source rocks for these oils remain unresolved although the source rocks are marine facies within the Cambrian and Ordovician strata with total thickness over 5 km. So far, there is no systematic classification of these oils on the basis of source facies. In this study, a practical approach was presented to select effective and sensitive biomarker parameters for source facies and maturity assessments for the studied oils on the basis of biomarker classification by hierarchical cluster analysis (HCA). Twenty-one terpanes and steranes in oils from both the Tabei (Northern Tarim) and Tazhong (Central Tarim) uplifts were classified into three groups using HCA on the basis of terpane and sterane concentrations. The result of biomarker grouping mainly reflects the differences in thermal stabilities among biomarkers for the 45 Tabei oils, providing a general thermal stability sequence for terpanes and steranes that helps the selection of effective maturity parameters. However, biomarker grouping suggests that both source facies and thermal stability have major influences on relative biomarker concentrations for the 75 Tazhong oils. The Tabei oils are mainly derived from a single source with relatively homogeneous facies while the Tazhong oils are derived from multiple sources or a single source with more heterogeneous facies. Based on the HCA results, twelve terpane and sterane ratios were selected as source facies parameters for the Tabei and Tazhong oils. These studied oils were consequently classified into four families by HCA and principle component analysis (PCA) integrating the twelve selected facies parameters of terpanes and steranes along with Pr/n-C17 and Ph/n-C18 ratios. Family 1 and 2 oils are mainly in the Tabei uplift while Family 3 and 4 oils are almost in the Tazhong uplift. Family 1 and 2 oils are derived from source rocks located at the northern, central and southern areas of the Northern Depression and the Tabei Uplift with marine mudstone facies. Family 3 and 4 oils are derived from source rocks located mainly at the southern area of the Northern Depression and the Tazhong Uplift with carbonate and evaporite facies. This study provides a practical approach to trace oil origins for oil and condensate reservoirs in the Tarim Basin and elsewhere.